2020
DOI: 10.1002/ccr3.3223
|View full text |Cite
|
Sign up to set email alerts
|

A neonate with intrauterine growth restriction and pseudo‐Bartter syndrome due to severe maternal eating disorder: A case report

Abstract: Pseudo-Bartter syndrome, a rare disorder, similar to Bartter syndrome, lacks renal tubular pathology. We present the case of a term small for gestational age neonate with metabolic alkalosis since birth with gradual decline within first week of life. Similar laboratory findings were observed in baby's mother, suffered from severe eating disorders. Pseudo-Bartter syndrome is a rare disorder caused by chloride poor diet, loss of sodium or chloride in the urine/ stool, and vomit or prostaglandin infusion. 1,2 It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…Five studies reported fetal pregnancy outcomes (see Table 4 ). Varying degrees of intrauterine growth restriction accounts for the most reported adverse fetal outcome [ 24 , 25 , 30 , 31 , 38 , 39 ]. Fetal distress was mentioned in one case report [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies reported fetal pregnancy outcomes (see Table 4 ). Varying degrees of intrauterine growth restriction accounts for the most reported adverse fetal outcome [ 24 , 25 , 30 , 31 , 38 , 39 ]. Fetal distress was mentioned in one case report [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the level of evidence, preterm birth [ 23 , 24 , 26 28 , 34 , 40 , 41 ], SGA birth [ 23 , 24 , 28 , 30 , 38 – 40 ], and low birth weight [ 24 , 25 , 27 29 , 39 ] were the most reported by the studies included. Three of the case reports that mentioned preterm birth were twin pregnancies [ 27 , 34 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Severe hyperemesis during pregnancy or alcoholism can also develop in the adult with PBS (1). In the pediatric field, neonatal-onset PBS has been anecdotally reported who were born to mothers with eating disorders and resultant malnutrition (6,7).…”
Section: Introductionmentioning
confidence: 99%